Against Oppression In Paul Verhouven's Black Book (2006)A Marxist Approach - SULISTYOWATI, DWI (2012)
The research paper is primarily intended to identify how the fight against oppression in Black Book (2006) viewed from Marxist perspective, and to analyze the movie based on its structural elements. The study in this research paper is descriptive qualitative. The data sources are divided into two, namely primary data sources and secondary data sources. The object of the study is a movie entitled Black Book directed by Paul Verhoeven The primary data sources is the movie of Black Book and the secondary data sources are information related to the primary data sources, books about Marxist approach and website. The techniques of data analysis are observation and library review. The technique of data analysis is descriptive technique. Based on the analysis the researcher comes to the conclusion as follows. First, based on the structural analysis Verhoeven in Black Book illustrated that "everyone has to fight against the oppression in his or her life to get freedom". Second, based on Marxist analysis it is evident that Verhoeven illustrates the fight against oppression of the people for their freedom.